Associations Between Serum Reproductive Hormone Concentrations and Hormonal Receptor Status Among Postmenopausal Chinese Women With Breast Cancer: An Observational Study - Jiang, Chuner; Wu, Peng; He, Xiangming; Ni, Jianfen; Ding, Xiaowen; Xu, Xiaohong; Wang, Fangzheng; Zou, Dehong (Frontiers in Oncology, 2022)
Background and Objectives Reproductive hormones and receptors play crucial roles in breast cancer development and progression. The association between preoperative serum reproductive hormone levels and receptor status in postmenopausal women with breast cancer remains unclear. Therefore, this study investigated the relationship between serum reproductive hormone concentrations and patient characteristics and hormone receptor status among postmenopausal Chinese women with breast cancer. Materials and Methods The medical records of 352 postmenopausal breast cancer patients who underwent an operation between October 2007 and October 2010 at the Department of Breast Tumor Surgery of Zhejiang Cancer Hospital were retrospectively evaluated. Serum levels of reproductive hormones were measured before surgery by liquid-chromatography tandem mass spectrometry. Hormone receptor levels were measured by an immunohistochemical assay using a mouse monoclonal antibody. The associations between serum hormone concentrations and hormone receptors were investigated by analysis of covariance. Results In this patient cohort, the serum level of luteinizing hormone (LH) declined with PMP duration. The median LH concentration was significantly higher in patients within 5 years of PMP than that in patients with PMP duration exceeding 5 years (23 vs. 18.32 mIU/ml, P <.0001). Significantly more patients with strong estrogen receptor (ER) or progesterone receptor (PR) expression had postmenopausal durations of less than 5 years compared to those with postmenopausal durations greater than 5 years (103 vs. 61 cases, P = .019; 93 vs. 46 cases, P = .0005). While most patients either lacked (97.1%) or co-expressed (84.3%) ER and PR, some patients expressed either ER or PR alone. ER and PR expression were negatively associated with receptor-tyrosine kinase erbB-2 (HER2) expression in postmenopausal patients with breast cancer. Meanwhile, increased ER and PR expression were associated with decreased serum levels of LH or follicle-stimulating hormone (FSH). Conclusion Decreased serum LH and FSH levels were associated with increased ER and PR expressions and decreased HER2 expression in postmenopausal patients with breast cancer.